The Effect of Communication Skills Training on Females Referred to Health Centers in Bahar; Applying the Social Support Theory for Increasing Marital Satisfaction Among Couples - Babak Moeini; Akram Karimi-Shahanjarini; Ali Reza Soltanian; Zahra Valipour Matlabi (Hamadan University of Medical Sciences, 2016)
Background and Objectives: Marital relationship has been regarded as one of the deepest types of communication. This study was performed to determine the effect of communication skills training on increasing marital satisfaction among couples by applying the social support theory on females referred to health centers in Bahar. Materials and Methods: This experimental study was performed on 100 females, referred to Bahar health centers in Hamadan province, during year 2016. For the sampling purposes, 100 females were randomly selected from health centers of Bahar city. The participants were randomly divided to 2 experimental and control groups (each group included 50 females). Data collection tools consisted of 3 questionnaires, including Enrich marital satisfaction questionnaires, social support questionnaire, and Burton communication skills questionnaire, which were completed through self-reporting by couples. An educational program in 3 sessions and 2 consulting classes were performed only for the intervention group and post-test questionnaires were completed after one month. Data were analyzed by SPSS-16 software using independent t test, paired t test, Fisher Exact test and Analysis of Covariance (ANCOVA). Results: Results showed that the mean scores of communication skills, marital satisfaction, and social support after the intervention were significantly increased in the experimental group compared to the control group (P<0.05). Conclusions: Communication skills training had a significant impact on improving marital satisfaction. One of the most important causes of this influence was social support by families. Therefore, it can be used as an effective intervention approach in this field.